Neurologic injuries in cycling and bike riding - Kennedy, J. (Physical Medicine & Rehabilitation Clinics of North America, 2009)
Cycling is often considered a leisurely activity with minimal potential for severe or chronic injury. Acute head and spinal trauma can be devastating and can predominantly contribute to all-cause mortality in injuries attributed to cycling. Chronic overuse injuries primarily affecting the ulnar, median, and pudendal nerves are also a cause of significant morbidity for the cyclist.